Structure, electronic structure, optical, and dehydrogenation catalytic study of (Zn1-zInz)(O1-xNx) solid solution - Mapa, Maitri; Sivaranjani, Kumarsrinivasan; Bhange, Deu S.; Saha, Biswajit; Chakraborty, Purushottam; Viswanath, Annamraju Kasi; Gopinath, Chinnakonda S. (Chemistry of Materials, 2010)
Indium and nitrogen codoping in ZnO leads to a solid solution of InN in ZnO with I composition of(Zn1-zInz)(O1-xNx). A simple solution combustion method has been adopted to prepare the above materials in less than 10 min with metal nitrates as the metal loll source and urea as fuel. With reference to ZnO, significant increase in lattice parameters was observed with increasing In-content. However, the In2O3 phase was Observed along with InN for]it content >= 10%. Optical absorption extended into the Visible region, at least LIP to 550 nm, demonstrates an effective reduction of optical band gap due to the formation of solid Solution. A new feature observed just above O2p valence band in X-ray photoelectron spectroscopy (XPS) suggests the creation of N 2p states from InN; the N Is core level XPS result too confirms nitride contribution. Raman spectroscopy and secondary ion mass spectrometry results show direct In-N, Zn-N. and In-N-Zn fragments in (Zn1-zInz)(O1-x,N-x). Catalytic activity explored for Oxidation of 2-butanol to ethyl methyl ketone demonstrates a high selectivity at 350 and 400 degrees C. All of the above characteristics suggest the multifunctional nature of (Zn1-zInz)(O1-xNx) and its potential for other applications.

Porosity driven photocatalytic activity of wormhole mesoporous TiO2-xNx in direct sunlight - Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Journal of Materials Chemistry, 2011)
Results obtained by combining four important factors simultaneously, namely, wormhole mesoporosity with low diffusion length for charge carriers, high surface area, nanoparticles with high crystallinity, and visible light absorption due to N-doping, in titania (meso-TiO2-xNx) are reported. Meso-TiO2-xNx materials have been prepared by a combustion method within 10 min and by varying urea : Ti(NO3)(4) between 1 (UT1) and 10 (UT10). All of the prepared materials have been thoroughly characterised. Nanocrystalline anatase phase with high surface area (234 m(2) g(-1)), and type-IV H-3-mesoporosity is observed with UT10. Photocatalytic rhodamine-B degradation was employed to screen for the activity of the materials, and p-anisyl alcohol oxidation to p-anisaldehyde was carried out successfully in aqueous solution under direct sunlight. High photocatalytic activity of UT10 in direct sunlight, in spite of high band gap (3.24 eV), is attributed to the better utilization of holes due to the low charge diffusion barrier associated with wormhole mesoporosity along with highly crystalline, however, nanoparticulate TiO2-xNx.

Gamma-Al2-xMxO3 +/- y (M = Ti4+ through Ga3+): potential pseudo-3D mesoporous materials with tunable acidity and electronic structure - Mathew, Thomas; Sivaranjani, Kumarsrinivasan; Gnanakumar, Edwin S.; Yamada, Yusuke; Kobayashi, Tetsuhiko; Gopinath, Chinnakonda S. (Journal of Materials Chemistry, 2012)
A simple and highly efficient surfactant-free sol-gel process has been developed to obtain nanocrystalline mesoporous gamma-Al2O3 and metal ion incorporated mesoporous gamma-Al2O3 with general formula gamma-Al2-xMxO3 +/- y (where M = Ti4+ through Ga3+). Any one of the first row transition metal (TM) ions along with Ga3+ could be introduced into the gamma-Al2O3 framework in a direct one-pot synthesis process. The generality of the present synthesis recipe for metal ion incorporation in gamma-Al2O3 was demonstrated by preparation of an Al-Ga-M ternary oxide system with the metal ion composition of general formula Al9GaTM (TM = Ti4+ to Zn2+) and their characterization through various physicochemical and spectroscopic techniques. The mesoporous gamma-Al2-xMxO3 +/- y materials showed a BET surface area in the range of 200-400 m(2) g(-1) with a narrow pore size distribution. Wormhole mesoporosity makes the material pseudo-3D (p3D) with a small pore depth of few nm (<10 nm). Metal ions in gamma-Al2O3 lead to changes in the acidity and electronic environment. XRD, TEM, and Al-27 MAS NMR studies demonstrate that the sol-gel process and the disordered mesoporous structure allow Ga and TM ions to be highly distributed and integrated in the gamma-Al2O3 framework. The efficacy of these materials in catalysis has been successfully evaluated for steam reforming of dimethylether: Ni, Cu and Zn containing Al9GaTM oxides showed high activity and stability. The smaller mesochannel depth (<10 nm) and pseudo-3D characteristics that arise due to the wormhole-type disordered mesoporous framework of these alumina materials facilitate mass transport through them without any leaching of metal ions out of the lattice and pore blocking during the reaction, which makes them attractive in catalysis. This preparation method is versatile enough to be used for a reproducible synthesis of metal ion incorporated mesoporous gamma-Al2O3 by varying the metal content and their combinations, and it is expected that many other metal ions could be introduced into the lattice framework for a variety of applications by tuning acidity and electronic structure.

Molecular oxygen-assisted oxidative dehydrogenation of ethylbenzene to styrene with nanocrystalline Ti1-xVxO2 - Sivaranjani, Kumarsrinivasan; Verma, Akrati; Gopinath, Chinnakonda S. (Green Chemistry, 2012)
Oxidative dehydrogenation of ethylbenzene to styrene has been studied with vanadium-incorporated mesoporous nanocrystalline titania (Ti1-xVxO2) and molecular oxygen between 440 and 530 degrees C. Incorporation of V in TiO2 lattice framework has been achieved by simple solution combustion method. Incorporation of V in TiO2 lattice has been confirmed by X-ray diffraction, XPS and Raman spectra and other physicochemical analysis. High ethyl benzene conversion and stable styrene yield has been observed with 10% V-containing rutile phase titania at 500 degrees C. However, stable but relatively lower styrene yield has been observed with 2 and 5% V-containing catalysts between 440 and 500 degrees C. Highest selectivity is observed with lower vanadium content. Comparable activity has been observed under similar experimental conditions with four times higher air-flow than that of O-2. In order to understand the structure activity relationship, spent catalysts were analyzed by all physico-chemical methods. Although there is a phase change from anatase to rutile Ti1-xVxO2 within 1 h of reaction, higher activity is primarily attributed to the ionic V5+ in Ti1-xVxO2 lattice, which prevents agglomeration to V2O5. It is to be underscored the reactivity is retained at the cost of textural properties and phase change from anatase to rutile, which is essential for the reaction.

Simple one pot synthesis of nano gold-mesoporous silica and its oxidation catalysis - Sekhar, A. C. Sunil; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Today, 2012)
A simple one pot synthesis strategy using a non ionic triblock copolymer P123 as reducing as well as templating agent has been employed to prepare nano gold particles incorporated in the pores of mesoporous silica catalyst. The catalyst is characterized by XRD, nitrogen adsorption desorption isotherms at 77 K and TEM. The presence of small gold nanopartilces (similar to 2-4 nm) clearly demonstrated that this strategy can be effective in incorporating Au inside mesochannels. The catalyst reduced at 300 degrees C in H-2 was found to be active for oxidation reactions, such as CO oxidation, and benzyl alcohol. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Alcohol oxidation; CO oxidation; Gold catalysis; Mesoporous silica

Toward a quantitative correlation between microstructure and DSSC efficiency: a case study of TiO2-xNx nanoparticles in a disordered mesoporous framework - Sivaranjani, Kumarsrinivasan; Agarkar, Shruti A.; Ogale, Satishchandra B.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2012)
The efficiency (eta) of a dye-sensitized solar cell (DSSC) depends on various parameters, the critical factors being a fast charge carrier transport and a slow rate of electron-hole recombination. The present article describes a simple combustion synthesis method to prepare TiO2-xNx with following four important features that directly influences eta: (1) a disordered mesoporous structural framework with high surface area to give high dye-loading and a small diffusion length for charge carriers allowing rapid movement to the surface; (2) electrically interconnected nanocrystalline TiO2-xNx particles with good necking and predominant (101) anatase facets to minimize electron-hole recombination; (3) low charge storage capacity in the titania framework; and (4) surface unsaturation assisting all the above factors. The pseudo-three-dimensional nature of mesoporous TiO2-xNx with the above features demonstrates the importance of textural features, and porosity allows faster diffusion of charge carriers to surface and their utilization to generate power. A quantitative correlation between interconnected nanoparticles over larger distances in a mesoporous framework and eta is demonstrated. This study also demonstrates an inexpensive and rapid method of producing the photoanode material with high eta in about 10 min.

Aminosilicate sol-gel stabilized N-doped TiO2-Au nanocomposite materials and their potential environmental remediation applications - Pandikumar, Alagarsamy; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S.; Ramaraj, Ramasamy (RSC Advances, 2013)
A facile chemical reduction method to synthesize amine functionalized silicate sol-gel-supported gold-deposited nitrogen-doped Degussa-TiO2 nanocomposite materials (APS/(N-P25-Au)(NCM)) is reported and the materials are characterized by DRS, PL, XRD, TEM, Raman, XPS and BET surface area analysis. The application of the synthesized APS/(N-P25-Au)(N)CM towards environmental remediation processes are investigated by studying the catalytic oxidation of carbon monoxide (CO) and photocatalytic reduction of toxic mercuric (Hg(II)) ions. The catalytic and photocatalytic activity of the prepared catalysts are found to be in the order of APS/(N-P25-Au)(NCM) >> APS/(P25-Au)(NCM) > N-P25 > P25. The enhanced catalytic and photocatalytic activities of the APS/(N-P25-Au)(NCM) can be attributed to the synergistic effect of Au-nps and N-doped P25. The catalytic activities of the APS/(N-P25-Au)(NCM) are very promising in the field of green technology for the environmental cleaning applications.

Disordered mesoporous V/TiO2 system for ambient oxidation of sulfides to sulfoxides - Negi, Sanjay Singh; Sivaranjani, Kumarsrinivasan; Singh, Anand Pal; Gopinath, Chinnakonda S. (Applied Catalysis A-General, 2013)
High sulfide conversion and predominant sulfoxide yield has been observed with 0.1% vanadium doped disordered mesoporous Ti1-xVxO2 material at ambient and sub ambient temperatures using environmentally green H2O2 oxidant. Ti1-xVxO2 materials were prepared by one-pot solution combustion method in less than 15 min and thoroughly characterized by X-ray diffraction, HRTEM, Raman spectra and other physicochemical techniques. Different sulfides, such as, phenylsulfide, methyl-p-tolylsulfide, ethylsulfide, thioanisole, were converted into the corresponding sulfoxide. Isolated V5+ incorporated in the TiO2 lattice is likely to be the active species for the sulfide oxidation reaction. Catalyst recycling studies indicates the robustness of the catalyst. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Ambient oxidation; Combustion synthesis; heterogeneous catalysis; Hydrogen peroxide; Mesoporous TiO2; Sulfoxidation; Sulfoxide

Disordered mesoporous TiO2-xNx+Nano-Au: an electronically integrated nanocomposite for solar H-2 generation - Sivaranjani, Kumarsrinivasan; Rajaambal, Sivaraman; Das, Tanmay; Roy, Kanak; Bhattacharyya, Somnath; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
We report on H-2 generation by photocatalysis driven by simulated white light by electronically integrated Au nanoparticles with multifunctional, disordered mesoporous TiO2-xNx (Au-NT) nanocomposites. Solar H-2 generation (1.5 mmolh(-1)g(-1)) from aqueous methanol has been demonstrated with Au-NT nanocomposites. The water splitting activity of Au-NT is attributed to the 21.1 ps lifetime of charge carriers observed from fluorescence lifetime measurements, which indicates a high electron-injection efficiency from nano-Au to the conduction band of TiO2, and hence charge separation as well as utilization. This is directly supported by the observation of a high photoluminescence emission intensity with Au-NT that highlights the energy transfer from nano-Au to TiO2. The p-n heterojunction observed between the Au (001) and TiO2 (101) facets helps to-wards the higher charge separation and their utilization. A low mesochannel depth (< 10 nm) associated with disordered mesoporous TiO2-xNx helps the charge carriers to move towards the surface for redox reactions and hence charge utilization. Visible-light absorption, as a result of the surface plasmon resonance of nano-Au, is observed in a broad range between 500 and 750 nm, which helps in harvesting visible-light photons. Finally, electronically integrated nano-Au with TiO2-xNx in Au-NT is evident from Raman and X-ray photoelectron spectroscopy measurements. All of these factors help to achieve a high rate of H-2 production. It is likely that a higher rate of H-2 production than that reported here is feasible by strategically locating Au clusters in porous TiO2 to generate hot spots through electronic integration.
Keywords: heterogeneous catalysis; Hydrogen; mesoporous materials; photochemistry; water splitting

Rational approach towards enhancing solar water splitting: a case study of Au-RGO/N-RGO-TiO2 - Bharad, Pradnya A.; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Nanoscale, 2015)
A rational approach was employed to enhance the solar water splitting (SWS) efficiency by systematically combining various important factors that helps to increase the photocatalytic activity. The rational approach includes four important parameters, namely, charge generation through simulated sunlight absorption, charge separation and diffusion, charge utilization through redox reaction, and the electronic integration of all of the above three factors. The complexity of the TiO2 based catalyst and its SWS activity was increased systematically by adding reduced graphene oxide (RGO) or N-doped RGO and/or nanogold. Au-N-RGO-TiO2 shows the maximum apparent quantum yield (AQY) of 2.46% with a H-2 yield (525 mu mol g(-1) h(-1)) from aqueous methanol, and overall water splitting activity (22 mu mol g(-1) h(-1); AQY = 0.1%) without any sacrificial agent under one sun conditions. This exercise helps to understand the factors which help to enhance the SWS activity. Activity enhancement was observed when there is synergy among the components, especially the simulated sunlight absorption (or one sun conditions), charge separation/conduction and charge utilization. Electronic integration among the components provides the synergy for efficient solar light harvesting. In our opinion, the above synergy helps to increase the overall utilization of charge carriers towards the higher activity.

Recent developments in solar H-2 generation from water splitting - Rajaambal, Sivaraman; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2015)
Hydrogen production from water and sunlight through photocatalysis could become one of the channels, in the not-so-distant future, to meet a part of ever growing energy demands. However, accomplishing solar water splitting through semiconductor particulate photocatalysis seems to be the `Holy Grail' problem of science. In the present mini-review, some of the critical strategies of semiconductor photocatalysis are focused with the aim of enumerating underlying critical factors such as visible light harvesting, charge carrier separation, conduction and their utilization that determine the quantum efficiency. We attempted to bring out the essential requirements expected in a material for facile water splitting by explaining important and new designs contributed in the last decade. The newly emerged designs in semiconductor architecture employing nanoscience towards meeting the critical factors of facile photocatalysis are elucidated. The importance of band gap engineering is emphasized to utilize potential wide band gap semiconductors. Assistance of metal nanostructures and quantum dots to semiconductors attains vital importance as they are exuberant visible light harvesters and charge carrier amplifiers. Benevolent use of quantum dots in solar water splitting and photoelectrochemical water splitting provides scope to revolutionize the quantum efficiency by its multiple exciton generation features. A list of drawbacks and issues that hamper the much needed breakthrough in photocatalysis of water splitting is provided to invite attention to address them and move towards sustainable water splitting.
Keywords: Hydrogen; nanomaterial; Photocatalysis; quantum dot; Semiconductor; visible light; water splitting